A high-elastic and high-moisture-resistant bonding rubber and preparation method thereof
By adding specific block copolymers and cellulose acetate fibers to the bonded rubber to form a crosslinked structure, the problem of deterioration of bonded rubber in a high humidity environment is solved, and the high elasticity and moisture resistance are improved.
Patent Information
- Application Number
- CN202410844890.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-27
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-06-27
AI Technical Summary
When used in high humidity environments for a long time, the viscosity decreases and lacks high elasticity and moisture resistance.
By adding ethylene-vinyl alcohol block copolymer and acrylic-acrylate block copolymer to the natural rubber/styrene butadiene rubber mixing system, a partially crosslinked ester structure is formed, elasticity and strength are improved, and cellulose acetate fibers are used as Toughening agent, replaces some fillers, improves overall mechanical properties and moisture resistance.
It achieves the effect of maintaining high viscosity and high elasticity in high humidity environments, while improving the airtightness and watertightness of the glue layer, ensuring the long-term and good performance of the bonded rubber.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the field of compound rubber, and in particular to a high-elasticity and high-moisture-resistant bonding rubber and a preparation method thereof. Background Art
[0002] Adhesive rubber is an important industrial raw material, which is usually obtained by mixing natural rubber and styrene-butadiene rubber. The main component of natural rubber is poly-cis-1,4-isoprene, and it also contains some other monomers as a copolymer system. In order to reduce the cost of adhesive rubber, a certain amount of filler is usually added to the system. The filler can provide basic wear resistance and hardness, and a small amount of addition has little effect on its viscosity.
[0003] Adhesive rubbers mainly composed of natural rubber and styrene-butadiene rubber have almost no active groups and can only achieve adhesion with materials such as metals after vulcanization. However, the vulcanized rubber has poor moisture resistance, and long-term use in a high humidity environment will cause its viscosity to decrease. Summary of the invention
[0004] In order to provide a bonding rubber that can maintain high viscosity and high elasticity under high humidity, the present application relates to a high-elasticity and high-humidity-resistant bonding rubber and a preparation method thereof.
[0005] First, the present application provides a high-elasticity and high-humidity-resistant rubber compound, the raw materials of which include the following components in parts by mass:
[0006] Natural rubber / styrene-butadiene rubber mixed system 100 parts
[0007] Neoprene 10-15 parts
[0008] 10-15 parts of ethylene-vinyl alcohol block copolymer
[0009] 25-30 parts of acrylic acid-acrylate block copolymer
[0010] Polyolefin 10-15 parts
[0011] Cellulose acetate fiber 15-20 parts
[0012] Inorganic filler 15-25 parts
[0013] 2-3 parts sulfur
[0014] 3-5 parts of accelerator
[0015] Lithium chloride 0.3-0.5 parts
[0016] The above raw materials are obtained by mixing in an internal mixer at a temperature not lower than 140° C. for at least 15 seconds.
[0017] In the above scheme, ethylene-vinyl alcohol block copolymer and acrylic acid-acrylate block copolymer are additionally added on the basis of the vulcanization of the natural rubber / styrene-butadiene rubber mixed system and chloroprene rubber, the purpose of which is to form a partially cross-linked ester structure of ethylene-vinyl alcohol block copolymer and acrylic acid-acrylate block copolymer in the system through mixing, on the one hand, the internal elasticity and strength are improved by the above cross-linked structure, and on the other hand, good air tightness and water tightness are provided. With the cross-linked system formed by ethylene-vinyl alcohol block copolymer and acrylic acid-acrylate block copolymer as the main body, by replacing part of the filler with cellulose acetate system, and using cellulose acetate fiber as a toughening agent with good strength, the whole system can be more uniform, and then the strength is also better guaranteed, so that the adhesive layer is not easy to crack.
[0018] In the above process, the prepared rubber compound has good moisture resistance as a whole. While maintaining good strength, the composite system formed by ethylene-vinyl alcohol block copolymer and acrylic acid-acrylate block copolymer can not only isolate the passage of oxygen and water vapor in the system, but also does not provide excessive additional hydroxyl structures for water molecules to hydrogen bond. In order to improve the softness of the system, the scheme adopts a combination of ethylene-vinyl alcohol block copolymer and acrylic acid-acrylate block copolymer, rather than simple polyvinyl alcohol and polyacrylic acid, so that the above system has moderate hardness and good rebound performance. In addition, the addition of polyolefin is also to provide better elasticity and softness. Although its contribution to elasticity is small, the addition of polyolefin greatly reduces the temperature required for processing, making the system less likely to denature during processing.
[0019] Furthermore, lithium chloride is added to the above system. In the system, lithium ions can form coordination with free hydroxyl and carboxyl groups in the system. On the one hand, it strengthens the formation of the cross-linking system and further improves the moisture resistance of the system, so that the viscosity and elasticity of the rubber will not be greatly lost after long-term use in a high-humidity environment. On the other hand, the lithium ion center also promotes the formation of overall elasticity.
[0020] In summary, the high-elasticity and high-humidity-resistant mixed rubber system in this scheme has good elasticity, mechanical strength and moisture resistance. It has good adhesion as a bonding rubber and can still maintain long-term good viscosity in a high humidity environment.
[0021] The inorganic filler is at least one of silicon dioxide, titanium dioxide, aluminum oxide, glass microspheres, glass fiber, and calcium carbonate.
[0022] Preferably, the molar content of ethylene monomer in the ethylene-vinyl alcohol copolymer is 35-42%.
[0023] The molar content of the ethylene monomer can well balance the softness, viscosity and elasticity of the system. The increase in the ethylene monomer content provides better softness, and within this range, it has a better maintenance effect on viscosity and moisture resistance.
[0024] Preferably, the molar content of acrylic acid monomer in the acrylic acid-acrylate block copolymer is 0.7 to 1 times the molar content of vinyl alcohol in the ethylene-vinyl alcohol block copolymer.
[0025] On the whole, the acrylic acid monomer is set to have a higher acrylic acid monomer content. Since the acrylic acid monomer has a high density, it cannot react with vinyl alcohol on each acrylic acid monomer, so it is easier to form a coordination structure of the lithium chloride center or couple with cellulose acetate fiber. In the above scheme, the combination of cellulose acetate and the rubber system is tighter, but too much acrylic acid monomer will cause the system acrylic acid-acrylate block copolymer to aggregate more on the surface of cellulose acetate, making the rubber layer more prone to cracking.
[0026] It should be noted that the above setting does not require that the total molar content of acrylic acid is greater than the total molar content of vinyl alcohol. Because acrylic acid will not completely undergo coupling reaction with vinyl alcohol under special circumstances such as steric hindrance and reaction conditions (nor is it expected that it will completely undergo coupling reaction with vinyl alcohol), in fact, there will be some excess hydroxyl groups in the system, but it will not cause a decrease in adhesion due to the adsorption of hydroxyl groups to water. On the contrary, since the hydroxyl groups form more hydrogen bond structures with the hydroxyl groups on the cellulose acetate fibers located inside the system (the total amount of hydroxyl groups in this part is larger), and only a small amount of free hydroxyl groups exist on the surface of the compound rubber, when they are bonded, a tight and moisture-resistant sealing structure can be formed. The good barrier properties of ethylene-vinyl alcohol itself further improve the sealing of the system.
[0027] Preferably, in the acrylic acid-acrylate block copolymer, the acrylate monomer is fatty alcohol acrylate, and more preferably, the acrylic acid-acrylate block copolymer is an acrylic acid-butyl acrylate block copolymer.
[0028] After experiments, it was found that the overall performance of acrylic acid-butyl acrylate block copolymer in the above system was better, and its comprehensive performance was more excellent than other acrylic acid-acrylic acid fatty alcohol esters.
[0029] Preferably, the density of the polyolefin is not greater than 0.91 g / cm 3 .
[0030] The use of lower density polyolefins can provide a softer system while improving the overall compatibility and resilience, making the system more fold-resistant.
[0031] Preferably, in the natural rubber / styrene-butadiene rubber mixing system, the mass fraction of natural rubber is 70 to 80 parts.
[0032] In the above scheme, the mass proportion of natural rubber is optimized to improve the overall strength, flexibility and compatibility of the system.
[0033] Preferably, in cellulose acetate, the acetylation ratio is 40 to 42%.
[0034] The acetylation ratio of cellulose acetate refers to the molar ratio of the acetylated hydroxyl groups on cellulose to the total hydroxyl groups. In this scheme, highly acetylated cellulose acetate is selected, which has better toughness, stronger folding resistance, and better maintenance effect on the elasticity of the system.
[0035] In addition, the present application also relates to a method for preparing the above-mentioned high-elasticity and high-humidity-resistant mixed rubber, comprising the following steps:
[0036] S1, mixing the natural rubber / styrene-butadiene rubber mixed system, ethylene-vinyl alcohol block copolymer and acrylic acid-acrylate block copolymer for the first time at a mixing temperature of 100-110° C. for 1-2 min;
[0037] S2, adding polyolefin, cellulose acetate fiber, chloroprene rubber and inorganic filler to the above system, heating to 140-150° C., mixing for 30-40 seconds to obtain a second mixing system;
[0038] S3, adding the remaining components except sulfur and accelerator to the second mixing system, cooling to 100-110° C., and continuing mixing for 2-3 minutes to obtain a third mixing system;
[0039] S4. Add sulfur and accelerator to the third mixing system, cool to 90-100° C., continue mixing for 1-2 minutes, and then discharge.
[0040] In the above scheme, the natural rubber / styrene-butadiene rubber mixed system, ethylene-vinyl alcohol block copolymer and acrylic acid-acrylate block copolymer are first mixed with other components. In this process, the ethylene-vinyl alcohol block copolymer and acrylic acid-acrylate block copolymer can be fully mixed first by using the mixing temperature. However, since there is no catalytic esterification component in the system, the reaction will not occur prematurely. In step S2, after the remaining components are added, the system is cross-linked to a certain extent through inorganic fillers and a small amount of active hydrogen on cellulose acetate fibers (in this process, the reactivity of hydroxyl groups on cellulose acetate fibers is slightly lower than that of ethylene-vinyl alcohol block copolymers), and then a uniform and good cross-linked structure is formed in the system, so that the ethylene-vinyl alcohol block copolymer and acrylic acid-acrylate block copolymer can better form a moisture-resistant and highly elastic elastomer system.
[0041] In step S2, the temperature needs to be raised to 140-150°C and kneaded for at least 15 seconds to promote the formation of the reaction system. More preferably, the kneading time in this step is preferably controlled at 2-3 minutes.
[0042] In summary, in the application, based on the natural rubber / styrene-butadiene rubber mixed system, ethylene-vinyl alcohol block copolymer and acrylic acid-acrylate block copolymer are added, and a large number of hydroxyl groups are introduced into the system to improve the bonding performance. At the same time, the effect of making it difficult for water vapor to penetrate the adhesive layer is achieved through the reaction system, thereby obtaining a mixed rubber with good elasticity, moisture resistance and folding resistance. DETAILED DESCRIPTION
[0043] The solution of the present application is further described through the following specific implementation methods.
[0044] Adhesion strength: Two layers of the prepared adhesive rubber were bonded together, and their 180° peel strength was measured.
[0045] Rebound rate: measured in accordance with ASTM-F36.
[0046] Moisture resistance: According to the bonding strength test method, after bonding two layers of adhesive rubber, place them in a moisturizing oven at 70°C and a relative humidity of not less than 90% for 480 hours (20 days), and then test the bonding strength.
[0047] Hardness: measured by Shore hardness tester at room temperature after molding.
[0048] Folding resistance: The above-mentioned adhesive rubber is prepared into a sheet with a thickness of 1 cm. It is tested by repeated folding (±50° angle), which can be carried out by a method similar to the sole folding resistance test (such as GB / T3903.1-2017 Footwear Whole Shoe Test Method Folding Resistance). A cut is pre-set before testing, and the cut length is 5 mm.
[0049] In the following scheme, all raw materials are commercially available products. For the convenience of description, some of the raw materials involved in this scheme are numbered as shown in Table 1.
[0050]
[0051] First, in Example 1, the types of selected ethylene-vinyl alcohol block copolymer and acrylic acid-acrylate block copolymer were tested, wherein in this example, the added mass of each component was as follows in terms of mass parts:
[0052] Natural rubber / styrene-butadiene rubber mixed system 100 parts
[0053] Neoprene 15 parts
[0054] 15 parts of ethylene-vinyl alcohol block copolymer
[0055] 30 parts of acrylic acid-acrylate block copolymer
[0056] Polyolefin 15 parts
[0057] Cellulose acetate fiber 15 parts
[0058] Inorganic filler 15 parts
[0059] 2 parts sulfur
[0060] 3 parts of accelerator
[0061] 0.3 parts of lithium chloride
[0062] Specifically, the inorganic filler in this scheme is fumed silica, the polyolefin is PE-SL, the accelerator is accelerator NS, and the acetylation degree of cellulose acetate fiber is 42%. In the above-mentioned vulcanization system, regarding the amount of sulfur and accelerator in the vulcanized rubber, the amount of sulfur added is controlled at 2 to 3 parts, and the amount of accelerator added is controlled at 3 to 5 parts. On the whole, it has a faster reaction rate and better reaction effect, and it is easy to form a better crosslinking degree in the system. Under normal circumstances, the addition of sulfur will increase the degree of crosslinking in the system and improve the cohesion, but it will also reduce the elasticity and processability, which will not be repeated in subsequent experiments.
[0063] The specific preparation method of the bonding resin in Example 1 is as follows:
[0064] S1, performing initial mixing of a natural rubber / styrene-butadiene rubber mixed system, an ethylene-vinyl alcohol block copolymer and an acrylic acid-acrylate block copolymer at a mixing temperature of 110° C. for 1.5 min;
[0065] S2, adding polyolefin, cellulose acetate fiber, chloroprene rubber and inorganic filler to the above system, heating to 140° C., and mixing for 40 seconds to obtain a second mixing system;
[0066] S3, adding the remaining components except sulfur and accelerator to the second mixing system, cooling to 110° C., and continuing mixing for 2.5 min to obtain a third mixing system;
[0067] S4. Add sulfur and accelerator to the third mixing system, cool to 96°C, continue mixing for 1 min, then discharge, and control the discharge port temperature to 160°C.
[0068] Specifically, in this scheme, the experimental scheme of selecting different ethylene-vinyl alcohol block copolymers and acrylic acid-acrylate block copolymers is shown in Table 2.
[0069]
[0070] The experiment was conducted on the experimental group in Example 1, and the results are shown in Table 3.
[0071]
[0072] In Example 2, relatively speaking, based on Example 1-1, the amounts of ethylene-vinyl alcohol block copolymer and acrylic acid-acrylate block copolymer were further adjusted, as shown in Table 4.
[0073]
[0074] By combining Example 1 and Example 2, it can be seen that in this solution, the combination of ethylene-vinyl alcohol block copolymer and acrylic acid-acrylate block copolymer can make the system have better mechanical strength and bonding strength, and still maintain good viscosity after long-term high humidity environment aging. In the above system, it is necessary to use ethylene-vinyl alcohol block copolymer and acrylic acid-acrylate block copolymer instead of simple vinyl alcohol and acrylate, the purpose of which is to improve the softness of the system and keep the system folding resistance and viscosity at a good level. Through realization, it can be seen that when the mass parts of ethylene-vinyl alcohol block copolymer are 10 to 15 parts and the mass parts of acrylic acid-acrylate block copolymer are 25 to 30 parts, the overall comprehensive performance is the best.
[0075] After adjusting the two polymers in Table 1, it can be seen that in the ethylene-vinyl alcohol block copolymer, the higher the proportion of ethylene, the lower the overall hardness, and the bonding performance is slightly reduced. At the same time, the moisture resistance shows a trend of first increasing and then decreasing. The reason is that the appropriate hydroxyl structure can just improve the sealing performance of the system, while too much hydroxyl structure is easy to cause the system to produce a water layer under the action of water, which has an adverse effect on the viscosity of the system. The molar content of the acrylic acid monomer used is preferably controlled within the range of 0.7 to 1 to the molar content of the vinyl alcohol monomer. Too much acrylic acid content will cause the system to be hard and the moisture resistance will decrease. Too little acrylic acid monomer will also cause the adhesion and moisture resistance to decrease. In addition, in the selection of acrylic acid-acrylate block copolymer, butyl acrylate is selected as the monomer for polymerization, and the obtained block copolymer has better comprehensive performance, and has better performance in viscosity, mechanical properties and softness.
[0076] Example 3. In this example, the ratio of fillers is studied. Specifically, on the basis of Example 1-1, while the total amount of cellulose acetate fiber and filler remains unchanged, the cellulose acetate fiber is replaced with fillers in equal mass, and cellulose acetate fiber with different acetylation degrees is replaced, and the experimental group shown in Table 5 can be obtained.
[0077]
[0078] From the experimental data in Table 5, it can be seen that in this scheme, the lower the acetylation degree of the acetate fiber, the better its viscosity, elasticity and folding resistance, but its moisture resistance will decrease slightly, but the decline range has a small impact on the overall performance. Taking all factors into consideration, the acetylation degree of cellulose acetate fiber in the range of 40-42% has the best experimental results. The amount of cellulose acetate fiber should be controlled at 15-20 parts. Too much cellulose acetate fiber will cause a certain decrease in moisture resistance and has no effect on improving the strength of the system, while too little cellulose acetate fiber will have an adverse effect on the overall performance and strength.
[0079] Example 4: In this example, the influence of the selection and dosage of polyolefin on the comprehensive properties of the system was studied. The specific experimental results are shown in Table 6.
[0080]
[0081] From the experimental data in Table 7, it can be seen that in this solution, the use of lower density polyolefins (such as ultra-low density polyethylene or polypropylene) can greatly improve the softness and folding resistance, and the overall hardness will also increase with the increase of density. Comprehensive experiments show that the added density is not higher than 0.91g / cm 3 All polyolefins can play a good role in softening the system, but excessive use of polyolefins will also lead to a decrease in the adhesion of the system.
[0082] Example 5. In this example, the mixing time and mixing temperature in step S2 are adjusted. The specific experimental groups are shown in Table 7.
[0083]
[0084] It can be seen from Table 7 that in step S2, it is not advisable to use too high a temperature and too long a time, otherwise it is easy to cause the system to be over-crosslinked, which makes it more difficult for the subsequently added materials to mix with the system. If the reaction time is too short or the temperature is too low, it will lead to insufficient crosslinking in step S2, which will have an adverse effect on the overall strength and moisture resistance of the system.
[0085] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A high elastic and high moisture resistance rubber compound, characterized in that: The raw materials include the following components by mass: Natural rubber / styrene-butadiene rubber mixed system 100 parts Neoprene 10-15 parts 10-15 parts of ethylene-vinyl alcohol block copolymer 25-30 parts of acrylic acid-acrylate block copolymer Polyolefin 10-15 parts Cellulose acetate fiber 15-20 parts Inorganic filler 15-25 parts 2-3 parts sulfur 3-5 parts of accelerator Lithium chloride 0.3-0.5 parts The above raw materials are processed by internal mixer at 140-150° C. for at least 15 seconds; The molar content of ethylene monomer in the ethylene-vinyl alcohol copolymer is 35-42%, and the molar content of acrylic acid monomer in the acrylic acid-acrylate block copolymer is 0.7-1 times the molar content of vinyl alcohol in the ethylene-vinyl alcohol block copolymer.
2. A high elastic and high moisture resistance rubber compound according to claim 1, characterized in that: In the acrylic acid-acrylate block copolymer, the acrylate monomer is fatty alcohol acrylate.
3. A high elastic and high moisture resistance rubber compound according to claim 2, characterized in that: The acrylic acid-acrylate block copolymer is an acrylic acid-butyl acrylate block copolymer.
4. The high elastic and high moisture resistance rubber compound according to claim 1, characterized in that: The density of the polyolefin is not greater than 0.91 g / cm 3 .
5. The high elastic and high moisture resistance rubber compound according to claim 1, characterized in that: In the natural rubber / styrene-butadiene rubber mixed system, the mass proportion of natural rubber is 70 to 80 parts.
6. The high elastic and high moisture resistance rubber compound according to claim 1, characterized in that: The inorganic filler is at least one of silicon dioxide, titanium dioxide, aluminum oxide, glass microspheres, glass fiber, and calcium carbonate.
7. The high elastic and high moisture resistance rubber compound according to claim 1, characterized in that: The acetylation ratio of the cellulose acetate is 40 to 42%.
8. The method for preparing the high elastic and high moisture resistance rubber compound according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: S1, mixing the natural rubber / styrene-butadiene rubber mixed system, ethylene-vinyl alcohol block copolymer and acrylic acid-acrylate block copolymer for the first time at a mixing temperature of 100-110° C. for 1-2 min; S2, adding polyolefin, cellulose acetate fiber, chloroprene rubber and inorganic filler to the above system, heating to 140-150° C., mixing for 30-40 seconds to obtain a second mixing system; S3, adding the remaining components except sulfur and accelerator to the second mixing system, cooling to 100-110° C., and continuing mixing for 2-3 minutes to obtain a third mixing system; S4. Add sulfur and accelerator to the third mixing system, cool to 90-100° C., continue mixing for 1-2 minutes, and then discharge.
Citation Information
Patent Citations
Sizing material for improving adhesive strength stability and preparation method thereof
CN106543490A
High-toughness anti-biting wear-resistant pet chewing toy rubber compound and preparation method thereof
CN112225955A